Characterising diel activity patterns to design conservation measures: Case study of European bat species. (January 2023) - Mariton, Léa; Le Viol, Isabelle; Bas, Yves; Kerbiriou, Christian
Abstract: Although diel activity time is a major axis of species' niche space, very few conservation measures focus on preserving daily periods free of anthropogenic pressures. While the spatial ecology of bats has received much attention, less is known about their temporal ecology, the knowledge being dispersed in studies of limited taxonomical, spatial and temporal range. We used data from the French bat monitoring program based on citizen science and standardised acoustic recordings (4409 sites monitored and 9807 nights monitored from 2014 to 2020) to characterise the diel activity patterns of 20 bat species so that their consideration in mitigation measures can help conservation. We designed a method to extract times of key descriptors and describe bat activity distribution throughout the night. We found that bat species could be separated in three functional groups characterised by a crepuscular activity, an activity that occurs when it is completely dark or an intermediate activity. We showed variations of diel activity patterns depending on season. We argue that accounting for these complex diel activity patterns would help design efficient mitigation measures, for instance to reduce the exposure of bats to light pollution or wind turbines. Overall, we advocate multi-taxa approaches to design conservation policies adapted to both the temporal and spatial distributions of species. Graphical abstract: Unlabelled Image Highlights: Conservation should include species temporal distribution besides their spatial one. Citizen science programs enable the study of bat diel activity patterns at wide scales. Similarities in diel activity patterns of bats enable functional groups to be defined. Seasons can interact with the time of night to determine diel activity patterns. Diel activity patterns should be considered when designing efficient mitigation measures.